The Discourse of Peer Review : Reviewing Submissions to Academic Journals - Paltridge, Brian (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book examines reports that are written by reviewers of submissions to a peer-reviewed journal. This includes a thorough study of the reports from the perspectives of context, content and genre, as well as from the point of view of pragmatics and politeness. The author examines the use of evaluative language, and the roles reviewers assume as they make their evaluations. He also explores how reviewers learn to write these reports. He then discusses the results of these analyses from the point of view of reviewer training, making suggestions for further research in the area of editorial peer review. The demystification of this occluded genre will be of benefit to doctoral students and early career academics not yet familiar with the peer review process, as well as those working in the broader areas of English for Specific Purposes and English for Academic Purposes, discourse analysis and writing for publication. Brian Paltridge is Professor of TESOL at the University of Sydney, Australia, where he teaches courses on writing for publication, thesis and dissertation writing, discourse analysis, and English for specific purposes. He is a co-editor of TESOL Quarterly and Editor Emeritus of English for Specific Purposes.- Resumé vydavatel
Keywords: vědecké časopisy; odborný jazyk; odborný styl; diskurzivní analýza; angličtina; scientific journals; professional language; professional style; discourse analysis; English language; elektronické knihy; monografie; electronic books; monographs